Electromyographic studies in abdominal exercises: a literature synthesis. - Monfort-Pañego M; Vera-García FJ; Sánchez-Zuriaga D; Sarti-Martínez MA (Journal of Manipulative & Physiological Therapeutics)
OBJECTIVE: The purpose of this article is to synthesize the literature on studies that investigate electromyographic activity of abdominal muscles during abdominal exercises performance. METHODS: MEDLINE and Sportdiscus databases were searched, as well as the Web pages of electronic journals access, ScienceDirect, and Swetswise, from 1950 to 2008. The terms used to search the literature were abdominal muscle and the specific names for the abdominal muscles and their combination with electromyography, and/or strengthening, and/or exercise, and/or spine stability, and/or low back pain. The related topics included the influence of the different exercises, modification of exercise positions, involvement of different joints, the position with supported or unsupported segments, plane variation to modify loads, and the use of equipment. Studies related to abdominal conditioning exercises and core stabilization were also reviewed. RESULTS: Eighty-seven studies were identified as relevant for this literature synthesis. Overall, the studies retrieved lacked consistency, which made it impossible to extract aggregate estimates and did not allow for a rigorous meta-analysis. The most important factors for the selection of abdominal strengthening exercises are (a) spine flexion and rotation without hip flexion, (b) arm support, (c) lower body segments involvement controlling the correct performance, (d) inclined planes or additional loads to increase the contraction intensity significantly, and (e) when the goal is to challenge spine stability, exercises such as abdominal bracing or abdominal hollowing are preferable depending on the participants' objectives and characteristics. Pertaining to safety criteria, the most important factors are (a) avoid active hip flexion and fixed feet, (b) do not pull with the hands behind the head, and (c) a position of knees and hips flexion during upper body exercises. CONCLUSIONS: Further replicable studies are needed to address and clarify the methodological doubts expressed in this article and to provide more consistent and reliable results that might help us build a body of knowledge on this topic. Future electromyographic studies should consider addressing the limitations described in this review.